Antioxidant efficacy of Kalanchoe daigremontiana bufadienolide-rich fraction in blood plasma in vitro. (1st December 2016) - Kolodziejczyk-Czepas, Joanna; Nowak, Pawel; Wachowicz, Barbara; Piechocka, Justyna; Głowacki, Rafał; Moniuszko-Szajwaj, Barbara; Stochmal, Anna
Abstract: Context: The main source of bufadienolides is toad venom; however, plants such as members of Kalanchoe Adans. (Crassulaceae) genus may also synthesize these bioactive substances. Objective: This is the first study on antioxidant effects and cytotoxicity of bufadienolide-rich fraction isolated from Kalanchoe daigremontiana Raym.-Hamet & H. Perrier. Materials and methods: The methanolic fraction was extracted from the plant roots and contained 0.48 mg bufadienolides/mg of dry mass (11α, 19-dihydroksytelocinobufagin, bersaldegenin-1-acetate, bersaldegenin-1, 3, 5-orthoacetate, 19-(acetyloxy)-3β, 5β, 11α, 14-tetrahydroxyl-12-oxo-bufa-20, 22-dienolide and 19-(acetyloxy)-1β, 3β, 5β, 14-tetrahydroxyl-bufa-20, 22-dienolide, mainly). The cytotoxicity of K. daigremontiana fraction was evaluated in an in vitro experimental model of blood platelets. The viability of blood platelets was determined on the basis of a release of lactate dehydrogenase. Results: The fraction scavenged DPPH radicals, with EC50 of 21.80 μg/mL. Studies on an experimental model of blood plasma under peroxynitrite-induced oxidative stress revealed that the plant preparation had moderate antioxidant properties. Levels of 3-nitrotyrosine and thiol groups indicated that the protective effect of K. daigremontiana was significant mainly for its concentration of 50 μg/mL. No effect was found in prevention of oxidation of low-molecular plasma thiols (glutathione, cysteine and cysteinylglycine). Simultaneously, measurements of lipid hydroperoxides and thiobarbituric acid-reactive substances (TBARS) indicated that the examined fraction might be effective antioxidant at broader concentration range, that is 1–5 and 25–50 μg/mL for hydroperoxides and TBARS generation, respectively. No cytotoxicity was observed at the concentration range of 1–50 μg/mL. Conclusions: Based on the obtained results, we suggest that antioxidant activity may additionally contribute to beneficial properties of K. daigremontiana -derived extracts.